Kinome-wide RNAi Screening to Identify Kinases Involved in Post-translational Modification of FUS - Liu, Serena E. B. (Université d'Ottawa / University of Ottawa, 2016)
Amyotrophic lateral sclerosis (ALS) is a devastating adult onset neurodegenerative disorder characterized by the selective degeneration of upper and lower motor neurons. Patients typically die from respiratory failures within 2-5 years after diagnosis. One of the milestones in ALS research is the discovery Fused in Sarcoma (FUS), an ALS causative gene. FUS is an RNA/DNA-binding protein and predominantly resides in the nucleus. Majority of the FUS mutations are located in the C-terminus and causing aberrant misdistribution to the cytoplasm. Currently, only a few binding partners of FUS are known, which makes it difficult to speculate on the function and interaction of the protein. In this study, we conducted a kinome-wide RNAi screen to identify kinases that affect the localization of FUS. A dual specificity protein kinase named CDC2-like kinase (CLK1) from the screen was found to be responsible for in post-translational modification of FUS and affects the localization of FUS in the nucleus. The identification of CLK1 as FUSmodifying kinase is consistent with roles ascribed to both in the binding and regulation of RNA.
Keywords: FUS; ALS; Kinome-wide RNAI Screen; Post-translational Modification